Uma história movida a álcool: impactos ambientais no contexto canavieiro paulista (1975 a 2003) - Bertazi, Marcio Henrique [UNESP] (2014)
The sugarcane, since its introduction in Brazil (after the rapid and voracious redwood trade) until the modern and specialized monoculture plantations, became an intrinsic and undeniable part of the Brazilian history, both in the economic sphere and in the imagination of successive generations. Generations those who watched an exponential income growth and an indelible depletion of natural resources, land concentration, rural migration and widespread unemployment. In this regard, the State of São Paulo gained relevance in the twentieth century, driven by the National Alcohol Program (Proálcool) and by the increase of alcohol demand in a context of global energy crisis. Consequently, the environmental impacts of the canicultor enterprise in this state. Although there is a great historical production on the issue of sugarcane in Brazil, including studies about Proálcool and its political, economic and social consequences, there is a significant lack of comprehensive surveys that map environmental impacts and put us in the lines of history. In this context, the analysis of the period extending from 1975 to 2003 revealed important movements in the Brazilian countryside, especially in the context of sugarcane in state of São Paulo. On one hand, there were established demands and trade-offs between country and city: the country pressed between the production of ethanol for domestic supply and the production of sugar for international market; and the city, which was as dependent of alcohol as Brazil was dependent of the oil in 1973. On the other hand, the social and environmental consequences become quite serious, among which: the intensification of the expulsion of rural workers to the cities with low locational infrastructure; atmospheric pollution and massive increase in the use of pesticides in the field, with direct consequences to the population health. In the analyzed period, however, there are...